Antiretroviral treatment Long-Term (ALT) cohort: a prospective cohort of 10 years of ART-experienced patients in Uganda. Issue 2 (21st February 2018) - Castelnuovo, Barbara; Mubiru, Frank; Kiragga, Agnes N; Musomba, Rachel; Mbabazi, Olive; Gonza, Paul; Kambugu, Andrew; Ratanshi, Rosalind Parks
Abstract : Purpose: Little information is available on patients on antiretroviral treatment (ART) after a long-term period from sub-Saharan Africa, with the longest follow-up and related outcomes being after 10 years on ART. At the Infectious Diseases Institute (IDI) (Kampala, Uganda), we set up a cohort of patients already on ART for 10 years at the time of enrolment, who will be followed up for additional 10 years. Participants: A prospective observational cohort of 1000 adult patients previously on ART for 10 years was enrolled between May 2014 and September 2015. Patients were eligible for enrolment if they were in their consecutive 10th year of ART regardless of the combination of drugs for both first- and second-line ART. Data were collected at enrolment and all annual study visits. Follow-up visits are scheduled once a year for 10 years. Biological samples (packed cells, plasma and serum) are stored at enrolment and follow-up visits. Findings to date: Out of 1000 patients enrolled, 345 (34.5%) originate from a pre-existing research cohort at IDI, while 655 (65.5%) were enrolled from the routine clinic. Overall, 81% of the patients were on first line at the time of the enrolment in the ART long-term cohort, with the more frequent regimen being zidovudine plus lamivudine plus nevirapine (44% of the cohort), followed by zidovudine plus lamivudine plus efavirenz (22%) and tenofovir plus lamivudine or emtricitabine plus efavirenz (10%). At cohort enrolment, viral suppression was defined as HIV-RNA <400 copies/mL was 95.8%. Future plans: Through collaboration with other institutions, we are planning several substudies, including the evaluation of the risk for cardiovascular diseases, the assessment of bone mineral density, screening for liver cirrhosis using fibroscan technology and investigation of drug–drug interactions between ART and common drugs used for non-communicable diseases.